Development of STEM-based Water Filters to Improve Water Quality in Pontang - Sari, Indah Juwita; Kambuna, Bening Nurul Hidayah; Nadillah, Sabrina; Madani, Willy Faisal; Auliya, Roudhatul; Wulandari, Atika (Gemilang Maju Publikasi Ilmiah (GMPI), 2025)
This study aimed to improve water quality in Pontang, Serang Regency, through the development of STEM (Science, Technology, Engineering, and Mathematics)-based water filtration. The method used a case study by conducting an observation of water conditions, designing and testing filters using local materials (cassava peel charcoal, zeolite, beach sand, white silica sand), as well as socialization and training for the community. The activities were carried out over six months (May to July 2025) involving the Family Welfare Empowerment (PKK) and Karang Taruna of Pontang. The results show that STEM-based water filters can improve water clarity, reduce odor, and are well received by the community. User response evaluations show a high level of satisfaction, especially regarding the ease of use and effectiveness of the tools. In conclusion, this innovation has the potential to be an applicable and sustainable solution for providing clean water.